Kajian Terhadap Naskah Kuna Nusantara Koleksi Fakultas Ilmu Pengetahuan Budaya Universitas Indonesia: Penyakit dan Pengobatan Ramuan Tradisional - Nawangningrum, Dina; Widodo, Supriyanto; Suparta, I Made; Holil, Munawar (Makara Human Behavior Studies in Asia, 2004)
From the manuscript, we can take the information about deseases and the medical treatment. The study of nusantara’s manuscripts which keep on the library Faculty of Humanities University of Indonesia (before Faculty of Letters-UI), especially medical text Javanese, Balinese, Melanese, and Sundanese show the information about the deseases, varieties of herba medical, processing, and therapies.